PERUBAHAN MAKNA NOMINA BAHASA ARAB DALAM AL-QURíAN: Analisis Sosiosemantik - Muhandis Azzuhri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2012)
This study discusses the changes in meaning of Arabic nouns in the Qur’an, including their forms, processes, and social implications. Sociosemantic theory, a combination of sociology and semantics, was employed in this research. The analysis compared the original forms of the words with their absorbed forms. The study found that meaning changes occur due to several factors: (a) linguistic aspects such as phonetics, morphology, and syntax; (b) historical factors; (c) socio-cultural factors; (d) psychological factors; (e) developments in science and technology; and (f) influence from foreign languages. These meaning changes have positive impacts on society’s mindset and understanding when studying the Qur’an. They provide a more comprehensive and integrative perspective, allowing a single word to have multiple interpretations.